Proposals for Improving Job Performance Through Employee Engagement at PT. X - Arumi, Anindita Daisy; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2012)
PT.X formed its business units in accordance with the development of a pregnant mother to give birth, while other business units were formed in accordance with the company’s concept.Currently PT. X is facing a problem where the number of customer complaints increased while the company’s profit decreased due to the low service performance given by the employees and the low knowledge needed to carried out the work. Corresponding with the problem, the research will see the employee engagement at PT.X, propose solutions to improve employee engagement, and the implementation plan.Questionnaire was distributed to the employees to determine the level of employee engagement in PT. X, which was formulated based on the Development Dimension International, American Society for Training and Development, Gallup, and Twelve Company Capabilities’ employee engagement models. Based on the questionnaire result, some solutions were proposed related to the human resource issues in PT. X.The proposed solutions were the setting up of data sharing system, job descriptions, standard operating procedures, product knowledge, feeedback system, training, performance criteria, and reward system. Keywords : employee engagement, job description, performance criteria, reward system.